In vitro generated Rhnull red cells recapitulate the in vivo deficiency: A model for rare blood group phenotypes and erythroid membrane disorders. Issue 5 (15th March 2013) - Cambot, Marie; Mazurier, Christelle; Canoui‐Poitrine, Florence; Hebert, Nicolas; Picot, Julien; Clay, Denis; Picard, Véronique; Ripoche, Pierre; Douay, Luc; Dubart‐Kupperschmitt, Anne; Cartron, Jean‐Pierre
<x xml:space="preserve">Abstract</x> Lentiviral modification combined with ex vivo erythroid differentiation was used to stably inhibit RhAG expression, a critical component of the Rh(rhesus) membrane complex defective in the Rhnull syndrome. The cultured red cells generated recapitulate the major alterations of native Rhnull cells regarding antigen expression, membrane deformability, and gas transport function, providing the proof of principle for their use as model of Rhnull syndrome and to investigate Rh complex biogenesis in human primary erythroid cells. Using this model, we were able to reveal for the first time that RhAG extinction alone is sufficient to explain ICAM‐4 and CD47 loss observed on native Rhnull RBCs. Together with the effects of RhAG forced expression in Rhnull progenitors, this strongly strengthens the hypothesis that RhAG is critical to Rh complex formation. The strategy is also promising for diagnosis purpose in order to overcome the supply from rare blood donors and is applicable to other erythroid defects and rare phenotypes, providing models to dissect membrane biogenesis of multicomplex proteins in erythroid cells, with potential clinical applications in transfusion medicine. Am. J. Hematol. 88:343–349, 2013. © 2013 Wiley Periodicals, Inc.